Formation of readiness of the physical education teacher of schoolchildren in Kazakhstan - N.E. Pfeyfer, R.Zh. Yerofeyeva,; Basharkina, E.A. (Opción, 2019)
The study aims to investigate a formation of readiness of the physical education teacher taking into account the gender features of schoolchildren in Kazakhstan via theoretical and practical research methods. As a result, there is a need for reconsideration of subject and methodical training of physical education teachers in higher educational institutions on the introduction of the disciplines helping to master the gender features of students. In conclusion, the majority of students at the beginning of the experiment did not have knowledge of gender pedagogy; they were not sufficiently informed about features of pupils and use this knowledge in professional activity.